Two new synonyms of Clematis hastata (Ranunculaceae), a species from the Daba mountains region in central China - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2020)
Based on the examination of herbarium specimens (including type material), we demonstrate that Clematis glabrifolia and C. hastata var. micrantha (Ranunculaceae) are identical with C. hastata, a species from the Daba mountains region in central China. We therefore place C. hastata var. micrantha and C. glabrifolia in synonymy with C. hastata herein.